Tranexamic Acid has no Effect on Post-Operative Hemarthrosis or Pain Control Following ACL Reconstruction Using Bone Patella Tendon Bone Autograft: A Double-Blind Randomized Controlled Double-Blind Trial (169). Issue 10 (31st October 2021) - Fried, Jordan; Bloom, David; Baron, Samuel; Hurley, Eoghan; Popovic, Jovan; Campbell, Kirk; Strauss, Eric; Jazrawi, Laith; Alaia, Michael
Objectives: Tranexamic acid (TXA) is a commonly used medication in orthopaedic procedures, reducing perioperative bleeding and need for transfusion. The purpose of this double-blind randomized controlled study was to evaluate if IV TXA for primary anterior cruciate ligament (ACL) reconstruction with bone-patella tendon-bone (BTB) could reduce perioperative blood loss or postoperative intra-articular hemarthrosis without postoperative drains. Methods: A controlled, randomized, double-blinded trial was conducted in 110 patients who underwent ACLR with BTB autograft. Patients were equally randomized to the control and experimental groups. The experimental group received two 1-gram boluses of IV TXA, one prior to tourniquet inflation and one prior to wound closure; the control group did not receive TXA. If a clinically significant hemarthrosis was evident, the knee was aspirated, and the volume of blood (ml) was recorded. Additionally, perioperative blood loss (ml); Visual Analog Scale (VAS) on postoperative days (POD) 1-7 and post-operative weeks (POW) 1, 6 and 12; postoperative opioid consumption POD 1-7; range of motion (ROM) and ability to straight leg raise (SLR) at POW 1, 6, 12; and pre and postoperative thigh circumference ratio (TCR). Results: There was no significant difference in perioperative blood loss between the experimental and control groups (32.5ml v. 35.6ml, p=0.47). The experimental group had 23 knees aspirated; control group had 26 knees aspirated (p=0.56). No significant difference seen in postoperative hemarthrosis volume with IV TXA (26.7ml v. 37.3ml, p=0.12). There was no significant difference in VAS score between the two groups (p=0.15), additionally, there was no difference in postoperative opioid consumption (p=0.33). There was no significant difference in ROM or ability to SLR, or pre- nor post-operative TCR (p > 0.05 for all). Conclusions: IV TXA in patients who undergo ACLR with BTB autograft does not significantly impact perioperative blood loss, postoperative hemarthrosis, or postoperative pain levels. Additionally, no significant differences were seen in early post-operative recovery regarding ROM or quadriceps reactivation.